Right Zygomaticomaxillary Complex Fracture With Rupture Of Internal Maxillary Artery: A Case Report - Herlambang, Beni; Budiman, Budiman (Jurnal Plastik Rekonstruksi, 2016)
Background: This case report gives prominence to the risk of delayed, possibly life - threatening bleeding following mid-facial fractures. Methods: A 42-year-old male was involved in an accident during which he suffered from right zygomaticomaxillary complex fractures with massive bleeding. The hemoglobin level was decreased from 11 to 5 g/dL, suspected caused by rupture of internal maxillary artery. Incidence of massive bleeding due to zygomaticomaxillary complex fracture is quite rare. Patient also felt right visual loss due to retrobulbar hematoma compression. He was given nasal tampon and transfusion in referral hospital. The patient had fracture reconstruction (reduction and fixation), ligation of right facial artery and temporary ligation of external carotid artery with Ethiloop for 5 days. Nevertheless, the bleeding still occurred. The patient then underwent Digital Subtraction Angiography (DSA) and coiling procedure from radiologic intervention. Twenty days after last procedure, we ligated the right external carotid artery due to recurrence of bleeding. Results: There are many modalities and procedure for the therapy of massive bleeding on midface fracture, ranging from conservative, minimal invasive to operative surgery. Patient that has gone through DSA procedure can still bleed. After ligation of external carotid artery, no more bleeding occurred. Conclusion: Patient suffering from extensive midfacial fracture, the internal maxillary artery and its branches are at special risk of injury due to their close anatomical relationship to bony structures. Its bleeding is possibly life threatening. Tampon and nasal packing are non-essential initial treatment, but digital pressure procedure can be performed to stop the bleeding temporarily. Ligation of external carotid artery is the best choice of treatment for permanent outcome.